Mejora de los procesos del área de ventas para optimizar el cumplimiento de los objetivos comerciales de la Empresa CIPEQ CIA LTDA - Aguirre Vera, Mercedes Viviana (2024)
The research work to improve the processes of the sales area to optimize the fulfillment of the commercial objectives of the company Cipeq Cia Ltda., reveals organizational deficiencies that affect operational efficiency. After analyzing interviews with the sales team, a lack of coordination and clarity in roles is observed, which has an impact on the quality of service. The central proposal consists of developing a Process Manual adapted to the needs of the company to improve operational coherence and define roles and responsibilities. The importance of implementing an action plan to address these challenges is highlighted, along with a culture of continuous improvement to maintain competitiveness. Recommendations include establishing a document management system, organizing team meetings, and conducting training to strengthen coordination and communication. These measures seek to optimize existing processes and lay the foundations for sustained growth in the commercial area.